PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, PERCEIVED SECURITY, DAN TRUST TERHADAP NIAT PENGGUNAAN E-WALLET DANA: STUDI BERBASIS TECHNOLOGY ACCEPTANCE MODEL (TAM) - Pratama, Ignatius Kevin Satya; Candiwan (eProceedings of Management, 2025)
The rapid growth of digital financial technology in Indonesia has accelerated the adoption of e-wallets aspractical, secure, and efficient payment tools. DANA, as one of the leading platforms, reached 200million users by 2024. However, this adoption is still challenged by concerns such as data security,complex user interfaces, and lack of service transparency. Therefore, this study is important to identifyseveral factors that influence user intentions to use DANA through an expanded TAM (TechnologyAcceptance Model) approach. This study has the main objective to determine the significant impact of perceived ease of use, perceivedusefulness, perceived security, and trust on behavioral intention in using DANA. This study also aims toanswer seven research questions that focus on the indirect and direct impacts of each variable in theTAM framework. Testing is conducted to understand how security and trust variables strengthen theeffectiveness of the TAM model in the context of digital financial services.This study uses a quantitative approach through causal design and survey methods. Primary data wereobtained by distributing questionnaires to 404 active DANA users. The analysis technique applied wasPLS-SEM (Partial Least Squares-Structural Equation Modeling). The validity and reliability of theinstrument were tested statistically, and hypothesis testing was carried out to evaluate the relationship ofeach variable in the theoretical model that had been developed.These findings show that all hypotheses are not statistically rejected. Trust is the most dominant variableto influence behavioral intention (β = 0.463), followed by perceived ease of use (β = 0.451). Perceivedusefulness and perceived security also have a significant impact, both indirectly on intention and directlyon trust. These findings strengthen the argument that perceived ease, usefulness, security, and trust are akey combination in predicting the adoption of financial technology such as e-wallets.This study concludes that trust is a foundational element in sustaining e-wallet usage. Practically, it isrecommended that DANA enhances the clarity of transactional information and improve theresponsiveness of customer service. Future studies are encouraged to use a longitudinal approach and toexplore the mediating role of trust and moderating effects of user demographics. Therefore, this studycontributes both theoretically to the development of TAM and practically to strategies for managing ewallet adoption in Indonesia.Keyword : Perceived Ease of Use, Perceived Usefulness, Perceived Security, Trust, Behavioural Intention